Acipenser baerii Brandt 1869 - Jouladeh-Roudbar, Arash; Ghanavi, Hamid Reza; Doadrio, Ignacio (Zenodo, 2020)
Acipenser baerii Brandt, 1869 – Non-native (Fig. 14) Acipenser baerii Brandt [J. F.] 1869: 115; Type locality: Ob and Lena river systems, Siberia, Russia. Syntypes: whereabouts unknown. Acipenser Nikolskii stenorrhynchus [A. M.] 1896: 400; Type locality: Large rivers of Siberia flowing to the Arctic. Syntypes: ZIN 10641 (2), 10885 (1), 10888 (1). ZISP 10641 also type of variety baicalensis. Acipenser stenorrhynchus var. baicalensis Nikolskii [A. M.] 1896: 401; Type locality: Lake Baikal, Siberia, Russia. Syntypes: MLSU 1631 (1), ZIN 10641 (2). Acipenser baeri hatys Dryagin [P. A.] 1948: 532; Type locality: From Lena to Kolyma rivers, Sakha-Yakutia, northeastern Russia. Syntypes: (27). Common name : Pr: Tas mahi baeri, En: Siberian sturgeon. Diagnosis : Extended snouts, four barbels in front of the mouth, the back is light grey to dark-brown colored, the belly color varies from white to clear yellow. Five rows of scutes, Small star-like scutes between the main ones. Clearly slit inferior lips. Meristic characters : D: 30–56, A: 17–33, GR: 20–49, DS: 10–12, LSC: 32–62, VS: 7–16. Distribution : Caspian Sea basin (Fig. 15). Introduced to Iran for aquaculture purpose. Usually individuals of this species escape from fish farms to water bodies. Presence in Iran inland water needs confirmation. Taxonomy . Conservation : IUCN: Endangered A2bcd+4bcd (Native population, Ruban and Zhu 2010), PC: Non-native, Not Applicable. Published as part of Jouladeh-Roudbar, Arash, Ghanavi, Hamid Reza & Doadrio, Ignacio, 2020, Fig. 4 in Fig. 4 in Fig. 3 in Fig. 21. Sesarmops mora n in Paralbunea dayriti, pp. 1-303 in Zoological Studies 59 (21) on page 13, DOI:10.6620/ZS.2020.59-21, http://zenodo.org/record/12822787